Objek Wisata Alam Spiritual Tamba Sunshine Waterfall Desa Tambakan, Kecamatan Kubutambahan, Kabupaten Buleleng - I Ketut Wardana Yasa (PARIWISATA BUDAYA: JURNAL ILMIAH PARIWISATA AGAMA DAN BUDAYA, 2019)
Tourist trend today exactly not only for recreation but how to find peacefull in their mind body and soul. That is why they interest in spiritual side. This chance is used by Mr Putu Budi Astrawan who are one of the tourism stakeholder in Bali. He build the nature spiritual objek that he give name Tamba Sunshine Waterfall which is located in Tambakan Village, Kubutambahan District, Buleleng Regency. The waterfall is around 30 meters high and the objek area is 50 are. There are seven water source around the object which are potentially to be a spiritual place future. There are some effort have been done to build this object such as build the garden, street and view point to see the waterfall. There are a plan to build a restaurant, inn and a place for yoga and meditation activities. There are some constraint such as technical and social constraint. But optimistically this object can be build succeslly in the future.